1977
DOI: 10.1111/j.1365-3091.1977.tb00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Algal crusts, autochthonous and clastic gypsum in a cannibalistic evaporite basin: a case history from the Messinian of Northern Apennines

Abstract: The Messinian Vena del Gesso Basin in the Northern Apennines is filled by very thick (up to 35 m) beds of coarse crystalline gypsum (selenite) associated with thinner carbonate and shaly (euxinic) intercalations. The conventional Usiglio model of salt fractionation does not apply to this evaporitic sequence for the following reasons: carbonate which underlies gypsum is not evaporitic but algal in origin; most gypsum did not precipitate from surface brines but at and below a sediment‐water interface occupied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(108 citation statements)
references
References 11 publications
1
107
0
Order By: Relevance
“…Desulphurisation of the polar fractions of the extracts of ten subsamples of the marl of the evaporitic cycle IV (Vai and Ricci Lucchi, 1977) of the Messinian Gessoso-solfifera Formation, Italy, released substantial amounts of gammacerane (O-200 pg/g TOC). Accordingly, large amounts of S-bound gammacerane must be bound in macromolecular aggregates present in the polar fraction.…”
Section: Resultsmentioning
confidence: 99%
“…Desulphurisation of the polar fractions of the extracts of ten subsamples of the marl of the evaporitic cycle IV (Vai and Ricci Lucchi, 1977) of the Messinian Gessoso-solfifera Formation, Italy, released substantial amounts of gammacerane (O-200 pg/g TOC). Accordingly, large amounts of S-bound gammacerane must be bound in macromolecular aggregates present in the polar fraction.…”
Section: Resultsmentioning
confidence: 99%
“…Very rare "spaghetti like" filaments (e.g. Vai and Ricci Lucchi, 1977;Panieri et al, 2010) have been observed.…”
Section: Sw Sectormentioning
confidence: 99%
“…10C). These features have been previously interpreted as early diagenetic products resulting from the displacive growth of coarse-grained selenite masses within the laminated matrix (Sturani, 1973;Clari et al, 2008), because in cross section they show an ellipsoidal shape that gives to the bed a characteristic flaser-nodular structure (embrechitic structure in Sturani, 1973;Vai and Ricci Lucchi, 1977) (Fig. 10D).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations